Study and interpretation of Rachmaninoff prelude in G minor OP.23 N0. 5 / Illi Diyana Mohd Isa - Mohd Isa, Illi Diyana (2011)
The title of my research topic: The INTERPRETATION OF RACHMANINOFF focuses more on the analysis and interpretation of piano playing. This research focuses on one piece from Rachmaninoff entitled Prelude in G minor op 23 No.5. Interpretation is more concerned about the sound than just the news. Thus, the aim in performance is to produce the kind of sound dial the musical context demands. A pianist should develop a sensitivity inside it is ears and fingers, so that he or she can gauge the possibilities of touch and tone in their varying qualities.